THE RELATIONSHIP BETWEEN ANEMIA AND EARLY ROPHYMUM IN BATARA SIANG PANGKEP GENERAL HOSPITAL FOR JANUARY 2019 – JUNE 2021 PERIOD - Nur Fatimah, Sry Mulya; Saharuddin; Nadyah Haruna (Alami Journal (Alauddin Islamic Medical) Journal, 2022)
Premature rupture of membranes (PROM) is the rupture of the fetal membranes before the onset of labor. The actual cause of PROM is still unclear, as much as 8% of all pregnancies are considered to be PROM. It is also evident that the main factor that causes perinatal mortality and morbidity was PROM. Therefore, a quick intervention is needed to control mortality and morbidity rate. The major purpose of this research was to investigate and understand the relationship between anemia and premature rupture of membranes at Batara Siang Regional Hospital of Pangkep. The methogological approach used in this study was an analytical observational research design with a case control approach. The sample of this study was inpartu mothers. The mothers who were diagnosed with PROM were taken as main cases, and those who were not diagnosed with PROM were taken as controls. The data collection of this study was the secondary research data taken from the medical records of Batara Siang Hospital. The data analysis was conducted using univariate and bivariate techniques by utilizing the Chi-Square Test. The samples obtained from this study were 68 samples. Therefore, from the results of this study, it was apparent that there was a significant relationship between hemoglobin and hematocrit with the occurrences of PROM. From this study, it was concluded that there was a relationship between anemia and the incidence of KPD.